2015
DOI: 10.2147/ppa.s79543
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health and diabetes awareness among Saudi diabetes patients

Abstract: PurposeThis study aimed to examine diabetic patients in Jeddah, Saudi Arabia, regarding their general diabetic and oral health-related awareness and practices, their awareness of the association of diabetes with periodontal disease, and their sources of diabetes-related information.MethodsDiabetic patients (n=454) who were receiving care at the diabetes clinic in King Abdulaziz University Hospital, Jeddah, Saudi Arabia, from October 2013 to May 2014, completed a six-part questionnaire assessing their sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 26 publications
12
60
5
5
Order By: Relevance
“…Or it could simply be that many dentists do not take on the responsibility of providing oral hygiene education and advice. Similar findings have been reported in many previous studies (Allen et al, 2008;Al Habashneh et al, 2010;Bahammam, 2015;Bowyer et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Or it could simply be that many dentists do not take on the responsibility of providing oral hygiene education and advice. Similar findings have been reported in many previous studies (Allen et al, 2008;Al Habashneh et al, 2010;Bahammam, 2015;Bowyer et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, about half of the respondents in this study have under-graduate or postgraduate degrees (48.5%), which probably reflects a higher level of general knowledge and awareness. Most of the studies that reported a lower level of awareness were conducted on diabetic patients visiting hospitals and outpatient clinics (Bahammam, 2015;Allen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of the respondents (58%) reported that they feel uncomfortable performing a simple periodontal examination which was more when compared to the findings of Asa′ad et al [18]. It was observed from similar studies, that medical practitioners are less interested in educating their patients on periodontal disease and its association with diabetes [14]. In our study, 11.5% residents stated that they never referred their patients to dentists for oral evaluation.…”
Section: Discussioncontrasting
confidence: 41%